Efficacy and Safety of Ibrutinib in Indian Patients with Relapsed or Refractory Chronic Lymphocytic Leukemia and Mantle Cell Lymphoma: Cases from a Named Patient Program - Agarwal, Mohan B; Bhurani, Dinesh; Shah, Chirag; Sood, Nitin; Singhal, Manish; Kamat, Anil; Chezhian, Subash; Mishra, Suryaprakash; Nagrale, Dinesh (Indian Journal of Medical and Paediatric Oncology, 2017)
Context: This named patient program evaluated the safety and efficacy of ibrutinib, a selective inhibitor of Bruton's tyrosine kinase in Indian patients with relapsed/refractory chronic lymphocytic leukemia (CLL, with/without chromosome 17 deletion [del17p]) and mantle cell lymphoma (MCL). Subjects and Methods: The eight enrolled patients (relapsed/refractory CLL: n = 6 [4/6 patients with del17p] and relapsed/refractory MCL: n = 2) had median age of 55 years (range, 52–60) and had received a median of 3 (CLL patients) and 4 (MCL patients) prior therapies. Patients received once-daily dose of ibrutinib (420 mg: CLL, 560 mg: MCL). Results: In CLL patients, the median time to response was 3 months (range, 0.5–7) and five of six patients had partial response (PR) whereas one achievedcomplete response (CR). Median time on treatment was 11.5 months (range, 8–14); five patients continued treatment and one was recommended stem cell transplantation (SCT). Of the two MCL patients, one achieved PR and one showed CR and advanced to SCT. In CLL patients, the median (range) hemoglobin level improved from 9.8 g/dL (7.2–11) at baseline to 12.0 g/dL (9.5–13.2) and median (range) platelet count improved from 150,000 cells/μL (21,000–195,000) at baseline to 190,350 cells/μL (130,000–394,000) at the time of analysis (July 2016). Most adverse events (AEs) reported were infections (n = 2). No Grade 3-4 or serious AEs, dose reductions, or treatment discontinuation due to AEs were reported. Conclusions: In this first real-world experience in Indian patients, ibrutinib demonstrated therapeutic efficacy in relapsed/refractory CLL (with/without del17p) and MCL. Safety results were consistent with the current known profile of ibrutinib.
Keywords: B-cell malignancies; Bruton's tyrosine kinase inhibitor; efficacy; ibrutinib; Indian; safety